Pengaruh Pengangguran, Sanitasi, TIK Terhadap IPM dan Melalui Kemiskinan Kabupaten/Kota di Kawasan Timur Indonesia 2021 - Lucya Hariani, Verga Herviana; Ekaria, Ekaria (Seminar Nasional Official Statistics, 2023)
Development Humans emphasize the fulfillment of a decent life both materially and non-materially. In measuring the achievement of human development, the Human Development Index (IPM) was formed. eastern of Indonesia (KTI) is an underdeveloped region and has lower human development achievements than western of Indonesia (KBI). In addition, KTI is the largest poverty contributing region which can trigger other problems. To fix this problem, the government has taken steps to accelerate development but until now it has not met the expected target. Therefore, this study aims to explain the general picture and analyze the influence of unemployment, sanitation infrastructure, ICT infrastructure directly on HDI or indirectly through district/city poverty in KTI 2021. The results of the path analysis show that unemployment, sanitation, and the internet have a direct effect on HDI and poverty, while unemployment, sanitation, and internet have an indirect effect on HDI through poverty.